2019
DOI: 10.1039/c9ta06219j
|View full text |Cite
|
Sign up to set email alerts
|

Amino-functionalised conjugated porous polymers for improved photocatalytic hydrogen evolution

Abstract: We introduced hydrophilic side chains into conjugated porous polymers and realised enhanced photocatalytic hydrogen evolution rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 60 publications
0
44
0
Order By: Relevance
“…It was found that the hydrogen bonds formed between nitrogen atoms and water molecules accelerate interfacial charge transfer from BBTÀ SC2NH2 to water. Lin et al [34] used tertiary amine groups to modify CPP, resulting in a hydrophilic CPP TrÀ F3N (Scheme 2) with improved photocatalytic performance. Compared to alkyl side chains modified TrÀ F8, the amino groups could bind with water through hydrogen bond and adsorb more water molecules, thus improving the hydrophilicity and water uptake ability, resulting in a great improvement in HER.…”
Section: Non-ionic Hydrophilic Conjugated Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the hydrogen bonds formed between nitrogen atoms and water molecules accelerate interfacial charge transfer from BBTÀ SC2NH2 to water. Lin et al [34] used tertiary amine groups to modify CPP, resulting in a hydrophilic CPP TrÀ F3N (Scheme 2) with improved photocatalytic performance. Compared to alkyl side chains modified TrÀ F8, the amino groups could bind with water through hydrogen bond and adsorb more water molecules, thus improving the hydrophilicity and water uptake ability, resulting in a great improvement in HER.…”
Section: Non-ionic Hydrophilic Conjugated Materialsmentioning
confidence: 99%
“…It was found that the hydrogen bonds formed between nitrogen atoms and water molecules accelerate interfacial charge transfer from BBT−SC2NH2 to water. Lin et al . used tertiary amine groups to modify CPP, resulting in a hydrophilic CPP Tr−F3N (Scheme ) with improved photocatalytic performance.…”
Section: Hydrophilic Conjugated Materials For Photocatalytic Applicatmentioning
confidence: 99%
“… 34 36 Due to the hydrophobic nature of most polymeric photocatalyst surface, wetting seems to be particularly important. 37 39 Several studies have shown that the introduction of polar groups results in materials with higher photocatalytic activities. 12 , 39 41 Large surface area to maximize the exposed surface to water can also be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“… 37 39 Several studies have shown that the introduction of polar groups results in materials with higher photocatalytic activities. 12 , 39 41 Large surface area to maximize the exposed surface to water can also be beneficial. Therefore, porous photocatalysts with high Brunauer–Emmett–Teller surface areas (SA BET ), namely, COFs and CMPs, 42 44 have been developed for photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Organic semiconducting polymer photocatalysts with excellent photocatalytic performance have attracted much interests for hydrogen evolution recently, owing to their diverse structural design, tunable functions, suitable electronic structure, and broad light harvesting in the visible region . In the past years, various organic polymer semiconductors with different structures and functions [e.g., conductive polymers (CPs), conjugated microporous polymers (CMPs), covalent triazine frameworks (CTFs), and covalent organic frameworks (COFs)] have been investigated as photocatalysts, and significant achievements have been obtained in the photocatalytic performance.…”
Section: Introductionmentioning
confidence: 99%